ANALYZING SERVICE ATTRIBUTES OF FOUR POINTS HOTEL MANADO USING IMPORTANCE AND PERFORMANCE ANALYSIS - Rumopa, Ferly; Tumbuan, Willem J. F. A.; Arie, Fitty V. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The number of hotels In Manado always increase. It creates the competition in hotel industry is more competitive. This research aims to analyze how important service attributes for the customer of Four Points Hotel Manado and how is the performance of service attributes of Four Points Hotel Manado. In order to determine the value of variables of service attributes, this research uses Importance and Performance Analysis in order to analyze the data. 100 guests who stayed there were surveyed as the respondents. The result shows there are employee attitude located in quadrant I it means the attributes has a high importance and low performance. Cleanliness, room price, location, and parking area are located in quadrant II which means these attributes has high importance and high performance. Hotel design, housekeeping service, restaurant and room facilities located in quadrant III which means these attributes are not importance and low performance. Internet located in quadrant IV it means this attributes is not importance but the performance is good. Based on the result there are recommendation for Four Points Hotel to keep maintain for those attributes that have high importance and high performance and improve those attributes that have low in performance.Â Keywords: marketing, service marketing, service attributes, importance and performance analysis.